The Urban and Rural Limitation Health Services Pregnant Mother’s on the Pandemic Covid-19, Papua Province of Indonesia - Irab, Semuel Piter; Makaba, Sarce; Irmanto, Maxsi; Bella, Sarni R.; Irjayanti, Apriyana; Rumaropen, Nova F.; Rumbiak, Helmin R. (Advances in Social Sciences Research Journal, 2022)
Coronavirus disease-19 (Covid-19), has become a pandemic and spread very quickly, reaching Indonesia and Papua Province. Impact covid-19, apparently influenced public health services, especially in a woman. A cross-sectional study design, to describe differences limitations in the pregnant mother’s health services urban and rural. Jayapura City and Jayapura Regency research sites. The sample was 90 pregnant mothers living in urban areas, and 90 pregnant mothers living in rural areas. Data analysis using Paired samples t-test. There were differences between urban and rural pandemics covid-19 (p-value = 0.020), there are limitations post integrated services health of the urban and rural (p-value = 0.049), community health centers urban and rural(p-value = 0.026), hospital health services urban and rural (p-value = 0.041), doctor/midwife health practices urban and rural (p-value = 0.019), antenatal care urban and rural (p-value = 0.000), and health services sick pregnant mothers for urban and rural (p-value = 0,000). Confirmation of covid-19 patients has increased, community compliance with implementing health protocols is low, it is increasingly difficult to break the chain of coronavirus transmission in the community, and health service units are limited to pregnant women in Papua Province.